Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Materi Warisan Budaya di Sekolah Dasar - Syarida, Sherly; Giwangsa, Sendi Fauzi; Somantri, Mubarok (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to analyze the implementation of differentiated instruction in improving student learning outcomes on Cultural Heritage topics in elementary schools. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that differentiated instruction effectively accommodates diverse learning styles—visual, auditory, and kinesthetic—making the learning process more inclusive and effective. This approach not only enhances academic achievement but also fosters active engagement, motivation, and student confidence. These results affirm the importance of student-centered learning strategies within the framework of the Merdeka Curriculum. The study implies the need for ongoing teacher professional development, supportive educational policies, and further research on the application of differentiated instruction across educational levels.